Effect of deep brain stimulation compared with drug therapy alone on the progression of Parkinson’s disease - Dong, Wenwen; Qiu, Chang; Lu, Yue; Luo, Bei; Jiang, Xu; Chang, Lei; Yan, Jiuqi; Sun, Jian; Liu, Weiguo; Zhang, Li; Zhang, Wenbin (Frontiers in Neuroscience, 2024)
Background: Parkinson's disease (PD) symptoms worsen as the disease progresses.Although deep brain stimulation (DBS) can effectively improve the motor symptoms of PD patients, it is not yet known whether DBS surgery, which is an invasive treatment modality, may change the progression of PD.The aim of this work was to compare the effect of DBS with that of drug treatment on the progression of PD.: A total of 77 patients with PD with the Hoehn and Yahr scale (HY) stage of 2.5 or 3 were included, and were divided into 34 in the drug therapy alone group (Drug-G) and 43 in the DBS therapy group (DBS-G). All patients were subjected to a follow-up of 2 years, and disease severity was assessed by the Unified Parkinson's Disease Rating Scale part III (UPDRS-III), the Montreal Cognitive Assessment (MOCA), the Hamilton Anxiety Scale (HAMA), and the Hamilton Depression Scale(HAMD) scores. In addition, the quality of life of patients and the burden on their family were assessed by the 39-item PD questionnaire (PDQ-39) scores, daily levodopa equivalent dose (LED), patient's annual treatment-related costs, and the Zarit Caregiver Burden Scale (ZCBS) score. The changes in relevant scale scores between the two groups were compared at each follow-up stage.The UPDRS-III score of the patients in the "off" state increased from year to year in both groups, and the degree of increase of this score was greater in the DBS-G than in the Drug-G group. The MOCA score in both groups began to decline in the 2nd year of follow-up, and the decline was greater in the Drug-G than in the DBS-G group. The PDQ39, LED, costs, and ZCBS were negatively correlated with the follow-up time in patients in the DBS-G group, and positively correlated with the follow-up time in patients in the Drug-G.PD is progressive regardless of treatment. DBS may accelerate the progression of the patient's disease, but the advantages of DBS are also evident. Indeed, DBS better improves patient's motor symptoms and quality of life and reduces the family burden. In addition, DBS has less impact on patients in terms of cognitive and mental effects.